1988
DOI: 10.1037/0278-6133.7.6.527
|View full text |Cite
|
Sign up to set email alerts
|

A cognitive-behavioral treatment for rheumatoid arthritis.

Abstract: This experiment tested a cognitive-behavioral rheumatoid arthritis treatment designed to confer skills in managing stress, pain, and other symptoms of the disease. We hypothesized that a mediator of the magnitude of treatment effects might be enhancement of perceived self-efficacy to manage the disease. It was predicted that the treatment would reduce arthritis symptoms and possibly would improve both immunologic competence and psychological functioning. The treatment provided instruction in self-relaxation, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
0
2

Year Published

1989
1989
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(134 citation statements)
references
References 29 publications
5
127
0
2
Order By: Relevance
“…In 11 trials (44%) (25,26,29,32,35,36,38,41,43,47,48), the assessor (i.e., data collector) was described as blinded to group assignment. Only 1 trial (43) described a proper method of allocation concealment.…”
Section: Resultsmentioning
confidence: 99%
“…In 11 trials (44%) (25,26,29,32,35,36,38,41,43,47,48), the assessor (i.e., data collector) was described as blinded to group assignment. Only 1 trial (43) described a proper method of allocation concealment.…”
Section: Resultsmentioning
confidence: 99%
“…In our research (8) it is significantly associated with health status in lupus patients. Problem solving was measured by an 11-item coping measure, adapted from the method described by Stone and Neale (51) for rheumatic disease patients (52). This measure assesses the frequency of use of problem-focused and emotionfocused coping strategies in managing common problems of rheumatic disease.…”
Section: Methodsmentioning
confidence: 99%
“…For example, cognitive behavioral therapy (CBT) for pain management has demonstrated that by improving self-efficacy, patients were more likely to report a reduction in pain and depressive symptoms and take their medication as prescribed (O'Leary, Shoor, Lorig, & Holman, 1988). Furthermore, CBT for children with JRA has been shown to reduce pain after the introduction of various self-regulatory techniques (Walco, Varni, & Ilowite, 1992).…”
Section: Psychological Treatmentmentioning
confidence: 99%